An Evaluation of Risk Management's Impact on University X's Performance - Vitra Puspita Dewi Hamzah; Eliza Fatima (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
Risk management has become an important element in efforts to improve university quality, especially in the era of globalization filled with challenges and uncertainties. This study aims to analyze the implementation of risk management at University X as a means to enhance the university's quality. This research focuses on the implementation of risk management at the Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), which implements the tri dharma of university in the form of research development and community service, and conducts an analysis using ISO 31000:2018. This research employs a qualitative descriptive method and a case study approach, collecting primary and secondary data through interviews, SOP documentation, and risk management guideline documentation. The research results show that the LPPM of University X has implemented the risk management process using ISO 9001:2015. The implementation of risk management by LPPM can be considered adequate; however, there are challenges such as the establishment of risk criteria, comprehensive risk identification, and the lack of integration of risk management into the strategic decision-making process. This research suggests the implementation of risk management at the university level to ensure the integration of risk management and the enhancement of risk management understanding within the university environment. This finding will help university education service, not limited to University X, to enhance their quality based on risk management.